MULTILAYERED CREATIVE ACTUALIZATION (THE POETIC DISCOURSE IN THE BILINGUAL COLLECTION MELANCHOLY BY EROL TUFAN) (Journal of Contemporary Philology, 2021)
This paper analyses the problem of bilingual authorship by taking into account the question of the author’s cultural affiliation and nationality. Erol Tufan is a poet that was born and raised in Macedonia, and after moving to Turkey continued to write in both languages (in Macedonian and Turkish). Since his poeticactivity is manifested in two languages, the question about the poet’s ontological affiliation is being raised, which in this case can be explained by the term “nomadic consciousness”, understood as a purest form of humanism. The bilingual collection of poems Melancholy highlights the phenomenon called “translingual writing”, or “self-translation”, as a reflection of the game of various linguistic codes, creating a text which is dynamic manifestation of several aspects of the poetic personality. In that sense, self-translation is a possibility of manifesting something more than a simple language correlate, since it is an act of creating a poetic self into another language. This fact poses the problem of the construction of author’s personality in the other (foreign) context. The vision of the poet as a nomad, migrant, the transculturalism and the author’s poetic reflections make Erol Tufan’s poetry an essential reading that belongs to the Macedonian literature, successfully avoiding the traps of linguistic coding and its limitations.
Keywords: bilingual authors; Erol Tufan; self-translation; transculturalism; liminality